Short-term sustained hypoxia induces changes in the coupling of sympathetic and respiratory activities in rats - Moraes, Davi José de Almeida; Bonagamba, Leni Gomes Heck; Costa, Kauê Machado; Costa-Silva, João Henrique; Zoccal, Daniel Breseghello [UNESP]; Machado, Benedito Honório (Wiley, 2014)
Individuals experiencing sustained hypoxia (SH) exhibit adjustments in the respiratory and autonomic functions by neural mechanisms not yet elucidated. In the present study we evaluated the central mechanisms underpinning the SH-induced changes in the respiratory pattern and their impact on the sympathetic outflow. Using a decerebrated arterially perfused in situ preparation, we verified that juvenile rats exposed to SH (10% O2) for 24 h presented an active expiratory pattern, with increased abdominal, hypoglossal and vagal activities during late-expiration (late-E). SH also enhanced the activity of augmenting-expiratory neurones and depressed the activity of post-inspiratory neurones of the Botzinger complex (B ¨ otC) ¨ by mechanisms not related to changes in their intrinsic electrophysiological properties. SH rats exhibited high thoracic sympathetic activity and arterial pressure levels associated with an augmented firing frequency of pre-sympathetic neurones of the rostral ventrolateral medulla (RVLM) during the late-E phase. The antagonism of ionotropic glutamatergic receptors in the BotC/RVLM abolished the late-E bursts in expiratory and sympathetic outputs of SH rats, ¨ indicating that glutamatergic inputs to the BotC/RVLM are essential for the changes in the ¨ expiratory and sympathetic coupling observed in SH rats. We also observed that the usually silent late-E neurones of the retrotrapezoid nucleus/parafacial respiratory group became active in SH rats, suggesting that this neuronal population may provide the excitatory drive essential to the emergence of active expiration and sympathetic overactivity. We conclude that short-term SH induces the activation of medullary expiratory neurones, which affects the pattern of expiratory motor activity and its coupling with sympathetic activity.